COVID-19: All Facts, No Myth - Pandey, K.R.; Rauniar, G.P. (Kathmandu University Medical Journal, 2020)
On December 31, 2019, the China Health Authority alerted WHO about 27 cases of pneumonia of unknown etiology in Wuhan City. It was subsequently named Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) and the disease as Coronavirus Disease 2019 (COVID-19). The disease has now become pandemic. Current review was done to summarize information on COVID-19 published in various scientific works. Electronic databases containing medical articles viz., MEDLINE/ PubMed, Google Scholar etc were searched using the Medical Subject Headings ‘COVID-19’, ‘2019- nCoV’, ‘coronavirus’ and ‘SARS-CoV-2’ during antecedent one year. All study designs were incorporated to harvest clinical, laboratory, imaging, and hospital course data. The intermediate host of the virus is still unknown. Respiratory droplets produced by the patient is main source of transmission. SARS-CoV-2 invades the airway epithelium by binding to angiotensin-converting enzyme-2 (ACE2) receptor with Coronavirus spike (S) protein. Most common symptoms are fever (98%), dry cough (77%), and dyspnea (63.5%). Later, complications like acute respiratory distress syndrome, septic shock etc may occur. Advanced age and co-morbidities like Diabetes have higher mortality otherwise Case Fatality Rate is 2-3%. RT-PCR is the diagnosis of choice. Since no universally accepted registered drug or FDA approved vaccine has come by now, prevention is the key. Hands should be regularly cleaned with soap or alcohol based sanitizer and in public, Nose and Mouth should be covered with face-mask and social distance of one meter should be maintained. While Vaccines are expected by early 2021, we should not forget to take comprehensive measures to prevent future outbreaks of zoonotic origin.